Dynamics Connectedness: TVP-VAR Insights into the Nexus between Selected Global Green Financial Instruments (Public Accounting and Sustainability, 2024)
Research aims: This study investigates the dynamics of connectedness among global green financial instruments driven by low-carbon policies. Design/Methodology/Approach: Employing the Time-Varying Parameter Vector Autoregressive (TVP-VAR) and Wavelet analysis, the researchers analyzed four primary variables derived from historical closing price indices, namely Global Carbon Efficient Index (SPGCEI), Global Clean Energy Index (SPGCE), Global Green Bond Index (SPGBI), and Global Sukuk Index (SPGSI). Daily data from January 2, 2015, to November 8, 2023, was considered. Data processing was then carried out utilizing E-Views 13 and R-Studio. Research Findings: The findings demonstrated that a low-carbon policy stimulates green financing through the stock market and increases the bond and sukuk for carbon reduction. Moreover, the study revealed that the dynamic connectedness level of all variables was 45.25%. While the SPGCEI and SPGBI act as net pairwise transmitters, the SPGCE and SPGSI function as net pairwise receivers. Theoretical Contribution/Originality: The study confirms that low-carbon policies drive green financing through stocks, promoting bond and sukuk activities for carbon reduction. By identifying the dynamic connectedness level and the roles of net transmitter and net receiver spillovers, it validates the impact of policies and introduces an innovative analytical framework for future research on the evolving dynamics of green finance. Policy Implication: The study recommends regulatory efforts to enhance connectedness and liquidity in green financial instruments to foster an effective and sustainable low-carbon ecosystem.